Development and performance evaluation of castor oil based biodiesel as an eco-friendly ester-based drilling fluid - Arain, A.H. (Taylor and Francis Ltd., 2022)
This study focuses on developing an efficient and environment-friendly drilling fluid using biodiesel as an alternative to the conventional diesel-based drilling fluid for drilling highly technical and challenging formations. The biodiesel was synthesized and produced from castor oil using the transesterification process. The physicochemical properties suggests that produced biodiesel has a high flashpoint (148 Â°C) and low pour point (-12 Â°C) compared to diesel oil. The synthesized biodiesel is utilized as a base oil to formulate an ester-based drilling fluid. A thorough experimental study is performed to evaluate the performance of formulated drilling fluid at ambient and reservoir temperature condition. A diesel-based drilling fluid is also formulated for comparative analysis. The experimental findings show that castor biodiesel-based drilling fluid's plastic viscosity and yield points are 10 and 25 higher than the diesel-based drilling fluid. However, the least filtrate loss volume is obtained for castor biodiesel-based drilling fluid than the diesel-based drilling fluid at high-temperature conditions. The filtrate loss by diesel-based drilling fluid was 17 and 9 higher than castor biodiesel-based drilling fluid at 25 Â°C and 100 Â°C, respectively. The results suggest the non-Newtonian and shear-thinning behavior of castor biodiesel-based mud (n < 1) associated with the HerschelâBulkley model. Â© 2022 Taylor & Francis Group, LLC.